The Role of Guidance Counseling Teacher and Parents in the Learning Process of Children with Special Needs of Slow Learners - Ilzam, Ahmadur; Purwoko, Budi (International Journal of Social Science and Religion (IJSSR), 2023)
Slow learners is a condition in students who cognitively have a capacity below the average normal child and are not included in the disability category, but slow learner children also have difficulties in coping with academic demands in regular classes. Slow learners do not have problems related to independent and social behavior, it's just that the IQ test or intelligence of students ranges from 70-90. For this reason, it is important for teachers and parents to take part by maximizing their role in the learning process of slow learner children. This study uses a qualitative method through literature study by collecting sources that are literary and used as a reference in this research. The aim of this research is to find out and understand things related to slow learner children and the role of guidance and counseling teachers and parents in these children. Meanwhile, the results of this research can be a reference regarding the effectiveness of guidance and counseling teachers and parents who take part when there are students who have special needs of the slow learner variety.